The differences between the direct and sol-gel syntheses of silicon-contained calcium phosphates - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2008)
Comparison of two experimental techniques of silicon-contained and/or silica-substituted calcium phosphate preparation from Ca(NO3)(2)center dot 4H(2)O, NH4H2PO4, fumed silica and aqueous solution of NH4OH was performed. The first technique was a traditional one, in which the final product was synthesized in an aqueous solution by the well-known sol-gel process, followed by phase separation, washing off, drying and high-temperature sintering. An environmentally friendly direct preparation route was the second technique, in which the initial chemicals were mixed in the necessary proportions inside a crucible, followed by a high-temperature sintering of the entire mixture. The sintered powders were analyzed by the standard measurement techniques. Intentional variations from the stoichiometry within +/- 10% of the amounts of the mixed chemicals were employed to compare the vulnerability of both preparation techniques to random fluctuations of the processing parameters. The results revealed a better reproducibility and a higher yield of the direct preparation technique but the traditional sol-gel technique was found to be able to compensate accidental technological imperfections.
Keywords: bioceramics; calcium phosphate; hydroxyapatite; tricalcium phosphate; silicon; direct preparation; sol-gel technique; IN-VITRO; BIOCERAMICS